The fourth time is murder - Havill, Steven (Havill, Steven. Posadas County series., 2008)
Undersheriff Estelle Reyes-Guzman is always busy, but more so now than ever. The sheriff is still not completely recovered from his stay in the hospital, and she is recovering from a hospital stay herself. After a long day at work, Estelle is happy to clear off her desk and drive home, where her beloved family waits. She hears her cell phone ringing as she pulls into the driveway. A truck has gone off the road and the driver's body found near the wreck. Back on the job, Estelle drives to the scene, where she finds more questions than answers. Was the truck's going over the hill really an accident? And why was there a single footprint on the man's body? An autopsy spurs further puzzles.